Construction and Practice of "Three Industry Integration and Three-dimensional Interaction" Talent Training System for Ship and Marine Engineering Specialty - Aixia Cao, Youwei Du, Ruiying Shao, Hongyuan Sun, Qiang Ma, Yuqin Tian (Forest Chemicals Review, 1970)
In response to the new round of scientific and technological revolution and industrial transformation, China has implemented a series of national strategies such as "Made in China 2025". Under the background of Marine power and the transformation of new and old energy, in order to better adapt to regional economic development, application-oriented undergraduate universities shall further integrate the development of specialty, industry and innovation and entrepreneurship, and implement the cooperative education mechanism of deep integration between school and enterprise and professional innovation and finance guided by market and social demand. Taking the naval architecture and marine engineering of Qingdao Huanghai University as the research object, taking the integration of specialty, industry and innovation and entrepreneurship as the path, the practice teaching system shall be gradually implemented to form the three-dimensional interactive teaching mode of students, teachers and enterprise experts, teaching, scientific research and social service, specialty, industry and innovation and entrepreneurship, thus constructing the innovative and applied talents training system of “three industries integration and three-dimensional interaction”. To cultivate innovative and applied talents in naval architecture and marine engineering equipment.